Highly resistant, impact and wear resistant concrete based on geopolymer cementitious systems and their applications
Patent Information
- Application Number
- CN202611427417.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]传统硅酸盐水泥基混凝土是目前工程应用最广泛的建筑材料,但存在固有性能缺陷:一方面水泥生产碳排放高、能耗大,不符合低碳建筑发展趋势;另一方面常规水泥混凝土孔隙结构疏松、界面过渡区薄弱,在高速水流冲磨、酸碱盐化学腐蚀、干湿交替、冻融循环等严苛工况下,极易出现表面剥落、骨料裸露、基体开裂、强度衰减等问题,使用寿命大幅缩短
本发明摒弃传统单一或二元固废复配模式,通过矿渣粉、偏高岭土、粉煤灰、煤矸石超细粉精准配比,互补活性组分优势,大幅提升铝硅酸盐活性,使聚合反应更充分,形成连续致密的三维网状凝胶结构,相较于常规地聚物混凝土,微观孔隙率降低35%以上,基体致密性大幅提升,从根本上改善抗渗透、抗腐蚀基础性能。
Smart Images

Figure CN123003202A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of new building materials and concrete engineering technology, and more specifically, to high corrosion-resistant, impact-resistant and wear-resistant concrete based on a geopolymer cementing system and its applications. Background Technology
[0002] Traditional silicate cement-based concrete is currently the most widely used building material in engineering, but it has inherent performance defects: on the one hand, cement production has high carbon emissions and high energy consumption, which does not conform to the development trend of low-carbon buildings; on the other hand, conventional cement concrete has a loose pore structure and a weak interface transition zone. Under harsh working conditions such as high-speed water flow abrasion, acid-alkali-salt chemical corrosion, alternating wet and dry conditions, and freeze-thaw cycles, it is very easy to cause problems such as surface spalling, aggregate exposure, matrix cracking, and strength reduction, resulting in a significant reduction in service life.
[0003] Geopolymer concrete is an inorganic cementitious concrete formed by alkali-activated polymerization of aluminosilicate solid waste as a precursor. It has advantages such as low carbon and environmental protection, high early strength, excellent corrosion resistance, and good thermal stability, making it a core green building material to replace traditional cement concrete. However, existing conventional geopolymer concrete has significant technical shortcomings: First, the polymerization reaction is poorly controllable, resulting in high micro-porosity, insufficient density, and poor resistance to high-speed impact and abrasion. Second, the matrix is brittle and lacks toughness, making it prone to micro-cracks that propagate under impact loads. Third, the compatibility between single fillers and the activation system is poor, and its resistance to sulfate, chloride, and acid-base composite corrosion is insufficient, failing to meet the long-term use requirements of high-intensity wear and strong corrosion conditions in water conservancy, chemical, and mining industries.
[0004] In existing technologies, most geopolymer concretes are prepared simply by compounding solid waste powders and alkali activators, without specifically optimizing the microstructure, interfacial properties, and the synergistic system of wear resistance and corrosion resistance. This results in a mismatch between wear resistance and corrosion resistance, toughness and strength, poor curing stability, and low finished product qualification rates, making large-scale application in high-demand engineering conditions difficult. Therefore, developing a geopolymer-based concrete with ultra-high corrosion resistance, impact and abrasion resistance, high toughness, and high stability to address the shortcomings of existing technologies is a pressing technical problem in this field. Therefore, we propose a high-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementitious system and its applications. Summary of the Invention
[0005] The purpose of this invention is to address the problems raised in the existing background technology. To achieve the above-mentioned objective, this invention provides the following technical solution: a high-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementitious system, prepared from the following raw materials in parts by weight: 380-450 parts of composite geopolymer precursor, 160-220 parts of composite alkali activator, 35-65 parts of wear-resistant and corrosion-resistant functional filler, 2.5-6 parts of flexible composite toughening fiber, 1250-1450 parts of composite aggregate, 3-5.5 parts of polycarboxylate superplasticizer, 0.8-1.8 parts of defoamer, and 80-110 parts of deionized water; The composite geopolymer precursor is a composite powder of ultrafine slag powder, metakaolin, fly ash and ultrafine coal gangue powder, with a mass ratio of 45:25:20:10. The composite alkali activator is a composite system of modified water glass and flake sodium hydroxide, and the modulus of the composite alkali activator is controlled to be 1.45 to 1.55. The wear-resistant and corrosion-resistant functional filler is a composite filler of nano-silica, silicon carbide micro powder and barite powder, with a mass ratio of 1:3:6.
[0006] As a preferred embodiment of the present invention, the composite geopolymer precursor has a particle size of 800–1200 mesh and a specific surface area ≥420 m². 2 / kg, of which the total content of activated alumina and activated silica is ≥88wt%, and the loss on ignition is ≤3.0wt%.
[0007] As a preferred technical solution of the present invention, the modified water glass is a potassium-sodium composite water glass with a Baume degree of 38-42Be′, a silicon dioxide content of ≥28wt%, and a total content of potassium oxide and sodium oxide of ≥13wt%; the sodium hydroxide is industrial flake high-purity sodium hydroxide with a purity of ≥99.0wt%.
[0008] As a preferred technical solution of the present invention, the particle size range of the wear-resistant and corrosion-resistant functional filler is 500-1000 mesh, wherein the particle size of nano-silica is 20-50nm, the purity of silicon carbide micro powder is ≥97wt%, and the barite powder has a barium sulfate content of ≥95wt%.
[0009] As a preferred embodiment of the present invention, the flexible composite toughening fiber is a mixture of polypropylene coarse fiber and basalt short fiber, with a mass ratio of 2:1; the polypropylene coarse fiber has a length of 12-18 mm and a diameter of 0.08-0.12 mm; the basalt short fiber has a length of 6-10 mm and a diameter of 0.05-0.09 mm.
[0010] As a preferred technical solution of the present invention, the composite aggregate is composed of fine aggregate and coarse aggregate. The fine aggregate is machine-made quartz sand with a fineness modulus of 2.6 to 3.0 and a mud content of ≤0.8wt%. The coarse aggregate is basalt crushed stone with a particle size of 5 to 25 mm and a crushing index of ≤8%. The mass ratio of fine aggregate to coarse aggregate is 3:7.
[0011] As a preferred embodiment of the present invention, the polycarboxylate superplasticizer is a powder superplasticizer with a water reduction rate of ≥30%; the defoamer is an organosilicon powder defoamer with an effective solid content of ≥98wt%.
[0012] The preparation method of high corrosion-resistant, impact-resistant and wear-resistant concrete based on geopolymer cementing system includes the following steps: S1. Pretreatment: Pour the composite geopolymer precursor, wear-resistant and corrosion-resistant functional filler and defoamer into a dry powder mixer and dry mix for 3-5 minutes to obtain a uniformly mixed dry powder. S2. Preparation of activating solution: Sodium hydroxide is slowly added to deionized water at room temperature and stirred until completely dissolved. Then modified water glass is added and stirred at a constant speed for 8-12 minutes. The mixture is then allowed to stand for 20-30 minutes to mature, thus obtaining a composite alkali activating solution with stable modulus. S3. Wet mixing molding: Add the composite aggregate into the mixing equipment and pre-mix for 2 minutes. Then add the dry powder obtained in step S1 and the polycarboxylate superplasticizer in sequence and mix for 3 minutes. Finally, slowly add the composite alkali activation liquid obtained in step S2 and continue mixing for 5 to 7 minutes until the slurry is uniform and free of agglomerates. S4. Fiber incorporation: Sprinkle flexible composite toughening fibers evenly into the mixing slurry and stir at low speed for 2-3 minutes to avoid fiber agglomeration and obtain concrete mix. S5. Pouring and curing: Pour the concrete mix into the mold, vibrate and compact it, smooth the surface, let it stand at room temperature until initial setting, cover it with a film to keep it moist for 7 days, and then let it cure naturally for 28 days to obtain the finished concrete.
[0013] As a preferred technical solution of the present invention, in step S5, the vibration frequency is 40-50Hz, the vibration time is 15-25s, the curing environment temperature is 20-28℃, and the relative humidity is ≥90%.
[0014] The application of high corrosion-resistant, impact-resistant, and wear-resistant concrete based on geopolymer cementing system is carried out in the pouring and repair of flood discharge structures for water conservancy and hydropower, riverbank protection, splash zones of port wharves, chemical acid and alkali corrosion-resistant floors, wear-resistant road surfaces for mining transportation, and anti-corrosion structures for sewage treatment plants.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention abandons the traditional single or binary solid waste compounding mode. By precisely proportioning slag powder, metakaolin, fly ash, and coal gangue ultrafine powder, the advantages of complementary active components are greatly enhanced, significantly improving the activity of aluminosilicate, making the polymerization reaction more complete, and forming a continuous and dense three-dimensional network gel structure. Compared with conventional polymer concrete, the micro porosity is reduced by more than 35%, and the matrix density is greatly improved, fundamentally improving the impermeability and corrosion resistance of the foundation.
[0016] This invention uses a composite filler of nano-silica, silicon carbide micro powder, and barite powder. The nano-components fill the micropores and optimize the gel structure, while the micron-sized silicon carbide improves the surface hardness and impact resistance, and the barite powder enhances the resistance to acid, alkali and salt corrosion. The three components work together to achieve the triple effect of "dense matrix, high hardness and wear resistance, and strong corrosion resistance", which solves the technical bottleneck of traditional materials that cannot achieve both wear resistance and corrosion resistance.
[0017] This invention uses a blend of coarse polypropylene fibers and short basalt fibers. The flexible fibers absorb impact energy and inhibit the propagation of microcracks, while the rigid fibers enhance the tensile and flexural strength and overall stability of the matrix. This dual approach addresses the defects of brittleness and poor impact resistance in geopolymer concrete, significantly improving structural stability under conditions of high-speed water flow and external impact.
[0018] This invention precisely controls the modulus of the composite alkali activator to the optimal range of 1.45 to 1.55, avoiding the problems of reaction lag and low strength caused by an excessively high modulus, and reaction too fast and matrix cracking caused by an excessively low modulus. It achieves a precise match between the polymerization reaction rate and the stability of the gel structure, and significantly improves the long-term durability of concrete.
[0019] This invention makes extensive use of industrial solid waste as the core raw material, without the addition of silicate cement, reducing carbon emissions by more than 60% compared to traditional wear-resistant concrete, making it green and low-carbon. The finished concrete has ultra-high resistance to sulfate corrosion, chloride ion penetration, acid and alkali corrosion, high-speed abrasion, and freeze-thaw resistance, making it suitable for various harsh working conditions such as water conservancy, chemical industry, mining, and ports. Its service life is 2 to 3 times longer than that of traditional cement-based wear-resistant concrete, and its industrialization value is extremely high. Attached Figure Description
[0020] Figure 1 This is a schematic block diagram illustrating the component fine distribution ratio provided by the present invention; Figure 2 This is a schematic block diagram of the preparation process provided by the present invention; Figure 3 A schematic block diagram illustrating the raw material composition provided by this invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0022] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely illustrates some embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. It should be noted that, in the absence of conflict, the embodiments and features and technical solutions in the embodiments of the present invention can be combined with each other. It should be noted that similar reference numerals and letters in the following figures indicate similar items; therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0023] Example 1: High-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system and its application, optimal embodiment, suitable for harsh working conditions of high-strength impact and abrasion and composite corrosion: A high-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system, with the following precise raw material ratio by weight: 400 parts of composite geopolymer precursor, 190 parts of composite alkali activator, 50 parts of wear-resistant and corrosion-resistant functional filler, 4 parts of flexible composite toughening fiber, 1350 parts of composite aggregate, 4 parts of powdered polycarboxylate high-efficiency water-reducing agent, 1.2 parts of organosilicon powder defoamer, and 95 parts of deionized water.
[0024] Precise parameter control of each core component: The composite geopolymer precursor is a compound of 800-1200 mesh ultrafine slag powder, metakaolin, grade I fly ash, and ultrafine coal gangue powder in a mass ratio of 45:25:20:10, with a specific surface area of 435 m². 2 / kg, total active silicon and aluminum content 89.2wt%, loss on ignition 2.1wt%; composite alkali activator is a mixture of potassium sodium composite water glass and high-purity flake caustic soda, with the modulus precisely controlled to 1.50, and water glass Baume degree 40Be′; wear-resistant and corrosion-resistant functional filler is a mixture of 30nm nano silica, 800 mesh silicon carbide micro powder and 600 mesh barite powder in a ratio of 1:3:6, with silicon carbide purity of 97.5wt% and barite barium sulfate content of 96wt%; flexible composite toughening fiber is a mixture of 15mm polypropylene coarse fiber and 8mm basalt short chopped fiber in a ratio of 2:1; composite aggregate is machine-made quartz sand with a fineness modulus of 2.8 and 5-25mm continuously graded basalt crushed stone, with a coarse-to-fine aggregate mass ratio of 3:7 and basalt crushing index of 7.2%.
[0025] Precise preparation process: S1. Dry powder pretreatment: Add all composite geopolymer precursors, wear-resistant and corrosion-resistant functional fillers, and defoamers to a forced dry powder mixer and dry mix at room temperature for 4 minutes at a stirring speed of 300 r / min to ensure no powder agglomeration and uniform mixing of components, eliminating the defects of ultrafine powder agglomeration; S2. Precise preparation of alkaline activation solution: At room temperature (25℃), slowly add high-purity flake sodium hydroxide to deionized water in portions and stir for 5 minutes until completely dissolved with no particle residue. Then, add potassium-sodium composite water glass at a uniform rate and continue stirring for 10 minutes. Seal and let stand for 25 minutes to eliminate internal stress in the solution and ensure that the modulus of the activation solution is stable without fluctuation; S3. Wet mixing and molding: First, add all composite aggregates and pre-mix for 2 minutes to optimize the aggregate gradation and compactness. Then, add the pretreated dry powder and polymer. Carboxylic acid water-reducing agent is stirred for 3 minutes to achieve uniform powder coating of aggregates. Finally, composite alkali activating liquid is slowly added dropwise at low speed, and stirring is continued for 6 minutes to control the slump of the slurry to 180-200 mm, ensuring that the mixture is uniform, without lumps or segregation. S4, Low-damage fiber incorporation: Composite toughening fibers are evenly dispersed into the slurry and stirred at a low speed of 150 r / min for 2.5 minutes to prevent fiber entanglement, agglomeration, and breakage, ensuring uniform three-dimensional fiber distribution. S5, Casting and precise curing: The mixture is poured into a test mold and vibrated with 45Hz variable frequency vibration for 20 seconds to completely remove internal air bubbles. The surface is then manually smoothed and polished. The mixture is then sealed and moisturized for 7 days at room temperature (25℃) and relative humidity (92%) to prevent moisture evaporation and subsequent matrix cracking. Natural curing is then carried out for 28 days to obtain the finished concrete. This embodiment is suitable for hydraulic spillways, high-silt, high-speed scouring hydraulic structures, and coastal high-corrosion and wear-resistant projects.
[0026] Example 2: High corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system and its application; an economical example suitable for conventional corrosion and mild erosion conditions: The raw material ratio by weight is as follows: 380 parts composite geopolymer precursor, 160 parts composite alkali activator, 35 parts wear-resistant and corrosion-resistant functional filler, 2.5 parts flexible composite toughening fiber, 1250 parts composite aggregate, 3 parts polycarboxylate superplasticizer, 0.8 parts defoamer, and 80 parts deionized water. The material composition, particle size, purity ratio, preparation process, and curing parameters of each raw material component are consistent with those in Example 1, only the amount of functional components and the amount of cementitious system are reduced to lower production costs. This formula has moderate viscosity and better workability, making it suitable for ordinary acid and alkali floors in chemical plants, conventional structures in sewage treatment plants, and lightly eroded riverbank protection, etc., where ultra-high strength requirements are lower but long-term corrosion and wear resistance is necessary in civil and general industrial projects.
[0027] Example 3: High-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system and its application; a high-strength, ultra-corrosion-resistant example suitable for extreme corrosion and ultra-high erosion conditions: By weight, the raw material ratio is as follows: 450 parts composite geopolymer precursor, 220 parts composite alkali activator, 65 parts wear-resistant and corrosion-resistant functional filler, 6 parts flexible composite toughening fiber, 1450 parts composite aggregate, 5.5 parts polycarboxylate superplasticizer, 1.8 parts defoamer, and 110 parts deionized water. The parameters of each raw material component, preparation process, and curing standards are the same as in Example 1. This example significantly increases the amount of cementitious materials, wear-resistant fillers, and toughening fibers, further optimizing the matrix density, impact toughness, and corrosion resistance. The micropores of the matrix are further refined, enabling long-term resistance to high-concentration acid-alkali-salt composite corrosion, high-speed high-silt scouring, and repeated freeze-thaw cycles. It is suitable for extremely harsh working conditions such as heavy-duty wear-resistant road surfaces in mines, high-salinity port splash zones, highly corrosive workshop floors in fine chemical plants, and large-scale flood discharge structures subjected to high-speed scouring.
[0028] Comparative Example 1, conventional single-polymer concrete, uses existing basic technology: traditional single metakaolinite as the sole precursor for the geopolymer, without a quaternary composite solid waste system, without adding nano-micro composite wear-resistant and corrosion-resistant fillers, without incorporating rigid-flexible composite toughening fibers, and only using a conventional sodium hydroxide-water glass single-activation system. The total amount of other cementitious materials, aggregate ratio, admixture dosage, preparation process, and curing environment are completely consistent with Example 1. This comparative example simulates the inherent defects of existing conventional polymer concrete technology, such as high matrix porosity, high brittleness, and poor wear and corrosion resistance. It serves as a comparison to highlight the inventiveness and performance improvement advantages of the composite system of this invention.
[0029] Comparative Example 2, conventional cement-based wear-resistant concrete, using existing mainstream commercial technology: Commercially available P·O 42.5 ordinary Portland cement is used to completely replace the geopolymer cementitious system of this invention. The proportions and dosages of wear-resistant functional fillers, composite fibers, aggregates, and admixtures are maintained exactly the same as in Example 1, and the mixing, pouring, vibration, and curing process parameters are standardized. This comparative example represents the most commonly used wear-resistant concrete formulation in current engineering projects, used to horizontally compare the performance advantages and low-carbon advantages of the geopolymer system of this invention compared to traditional cement-based materials.
[0030] Standardized Performance Testing Scheme: All sample performance tests in this invention adhere to current national and industry authoritative standards: Concrete compressive and flexural strength are tested according to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50082-2009); abrasion resistance is tested according to the high-speed impact abrasion test method in the "Test Procedure for Hydraulic Concrete" (SL 352-2020), and the abrasion per unit area is statistically analyzed; permeability resistance and chloride ion diffusion coefficient are tested according to the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete"; sulfate corrosion resistance and freeze-thaw resistance are tested using the accelerated aging test method specifically for hydraulic concrete, measuring the strength loss rate after corrosion and freeze-thaw cycles. All samples are prepared as 100mm×100mm×100mm cubic blocks and 100mm×100mm×400mm prismatic blocks, with three parallel samples per group. The average value is taken as the final test result to eliminate experimental errors, ensuring accurate and reliable data. The performance results of each sample after 28 days of standard curing are as follows: Example 1 Sample: Compressive strength 68.5 MPa, flexural strength 8.2 MPa, abrasion rate 0.12 kg / m 2 The chloride ion diffusion coefficient is 2.1 × 10⁻¹³ m. 2 / s, sulfate corrosion strength loss rate 1.8%, strength loss rate after 200 freeze-thaw cycles 2.3%; balanced overall performance, suitable for most harsh working conditions, making it the best cost-effective formula.
[0031] Example 2 sample: compressive strength 62.3 MPa, flexural strength 7.5 MPa, abrasion rate 0.15 kg / m 2 The chloride ion diffusion coefficient is 2.5 × 10⁻¹³ m. 2 / s, sulfate corrosion strength loss rate 2.2%; performance meets the requirements of conventional industrial anti-corrosion and wear-resistant conditions, lower production cost, and suitable for large-scale popular application.
[0032] Example 3 sample: compressive strength 71.2 MPa, flexural strength 8.6 MPa, abrasion rate 0.10 kg / m 2 The chloride ion diffusion coefficient is 1.9 × 10⁻¹³ m. 2 / s, sulfate corrosion strength loss rate 1.5%; overall durability, wear resistance and mechanical properties are optimal, and it can withstand extremely complex and harsh working conditions.
[0033] Comparative Example 1 (conventional single geopolymer): compressive strength 45.6 MPa, flexural strength 4.3 MPa, abrasion rate 0.38 kg / m² 2 The chloride ion diffusion coefficient is 8.6 × 10⁻¹³ m. 2 / s, sulfate corrosion strength loss rate 7.8%; poor matrix density and insufficient toughness, significant defects in wear and corrosion resistance, making it unsuitable for harsh working conditions.
[0034] Comparative Example 2 (conventional cement-based wear-resistant concrete): compressive strength 56.8 MPa, flexural strength 6.1 MPa, abrasion rate 0.29 kg / m² 2 The chloride ion diffusion coefficient is 5.3 × 10⁻¹³ m. 2 / s, sulfate corrosion strength loss rate 5.2%; durability and impact resistance are far lower than those of this invention, and carbon emissions are high, and it is prone to cracking and peeling after long-term use.
[0035] The standardized test data clearly verify that this invention, through the synergistic innovation of a quaternary composite geopolymer precursor, a precise modulus alkali-activated system, multi-level wear-resistant and corrosion-resistant fillers, and rigid-flexible composite fibers, constructs a dense and stable three-dimensional gel matrix. This completely solves the technical shortcomings of traditional geopolymer concrete, such as high brittleness, high porosity, and the inability to simultaneously achieve wear and corrosion resistance. Furthermore, it significantly outperforms traditional cement-based wear-resistant concrete. The mechanical properties of concrete produced by this invention are improved by 20%–50%, abrasion loss is reduced by more than 50%, ion permeability coefficient is reduced by more than 70%, corrosion strength loss rate is significantly reduced, and long-term service stability is extremely strong. Simultaneously, it boasts high solid waste utilization, low carbon emissions, and environmental friendliness. The process is simple and easy to mass-produce, possessing extremely high engineering promotion value.
[0036] Specific applications: The concrete of this invention can be directly mixed and poured for hydraulic structures such as flood discharge channels, overflow dams, and river erosion slope protection, resisting the erosion of high-speed water flow and sediment and corrosion from the aquatic environment; it can be used for structures in the splash zone and tidal zone of ports and wharves, resisting the corrosion of chloride ions from seawater and the erosion of waves; it can be used for the flooring of acid and alkali storage tanks and the anti-corrosion layer of reaction pools in chemical plant areas, withstanding long-term acid and alkali media corrosion; at the same time, it can be applied to wear-resistant and anti-corrosion projects such as mine transportation roads and sewage treatment plant structures. After casting, no additional anti-corrosion and wear-resistant treatment is required, making construction convenient and with a long service life.
[0037] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described herein. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the specific embodiments described above. Therefore, any modifications or equivalent substitutions to the present invention, as well as all technical solutions and improvements that do not depart from the spirit and scope of the invention, are covered within the scope of the claims of the present invention.
Claims
1. A high-corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system, characterized in that, It is prepared from the following raw materials in parts by weight: 380-450 parts of composite geopolymer precursor, 160-220 parts of composite alkali activator, 35-65 parts of wear-resistant and corrosion-resistant functional filler, 2.5-6 parts of flexible composite toughening fiber, 1250-1450 parts of composite aggregate, 3-5.5 parts of polycarboxylate superplasticizer, 0.8-1.8 parts of defoamer, and 80-110 parts of deionized water; The composite geopolymer precursor is a composite powder of ultrafine slag powder, metakaolin, fly ash and ultrafine coal gangue powder, with a mass ratio of 45:25:20:
10. The composite alkali activator is a composite system of modified water glass and flake sodium hydroxide, and the modulus of the composite alkali activator is controlled to be 1.45 to 1.
55. The wear-resistant and corrosion-resistant functional filler is a composite filler of nano-silica, silicon carbide micro powder and barite powder, with a mass ratio of 1:3:
6.
2. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The composite geopolymer precursor has a particle size of 800–1200 mesh and a specific surface area ≥420 m². 2 / kg, of which the total content of activated alumina and activated silica is ≥88wt%, and the loss on ignition is ≤3.0wt%.
3. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The modified water glass is a potassium-sodium composite water glass with a Baumé degree of 38-42Be′, a silica content of ≥28wt%, and a total potassium oxide and sodium oxide content of ≥13wt%; the sodium hydroxide is industrial flake high-purity sodium hydroxide with a purity of ≥99.0wt%.
4. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The wear-resistant and corrosion-resistant functional filler has a particle size range of 500-1000 mesh, of which the nano-silica particle size is 20-50 nm, the silicon carbide micro powder purity is ≥97 wt%, and the barite powder barium sulfate content is ≥95 wt%.
5. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The flexible composite toughening fiber is a mixture of polypropylene coarse fiber and basalt short fiber, with a mass ratio of 2:1; the polypropylene coarse fiber has a length of 12-18 mm and a diameter of 0.08-0.12 mm; the basalt short fiber has a length of 6-10 mm and a diameter of 0.05-0.09 mm.
6. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The composite aggregate consists of fine aggregate and coarse aggregate. The fine aggregate is machine-made quartz sand with a fineness modulus of 2.6 to 3.0 and a mud content of ≤0.8 wt%. The coarse aggregate is basalt crushed stone with a particle size of 5 to 25 mm and a crushing index of ≤8%. The mass ratio of fine aggregate to coarse aggregate is 3:
7.
7. The high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementing system according to claim 1, characterized in that, The polycarboxylate superplasticizer is a powder superplasticizer with a water reduction rate of ≥30%; the defoamer is an organosilicon powder defoamer with an effective solid content of ≥98wt%.
8. A method for preparing high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementitious system as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Pretreatment: Pour the composite geopolymer precursor, wear-resistant and corrosion-resistant functional filler and defoamer into a dry powder mixer and dry mix for 3-5 minutes to obtain a uniformly mixed dry powder. S2. Preparation of activating solution: Sodium hydroxide is slowly added to deionized water at room temperature and stirred until completely dissolved. Then modified water glass is added and stirred at a constant speed for 8-12 minutes. The mixture is then allowed to stand for 20-30 minutes to mature, thus obtaining a composite alkali activating solution with stable modulus. S3. Wet mixing molding: Add the composite aggregate into the mixing equipment and pre-mix for 2 minutes. Then add the dry powder obtained in step S1 and the polycarboxylate superplasticizer in sequence and mix for 3 minutes. Finally, slowly add the composite alkali activation liquid obtained in step S2 and continue mixing for 5 to 7 minutes until the slurry is uniform and free of agglomerates. S4. Fiber incorporation: Sprinkle flexible composite toughening fibers evenly into the mixing slurry and stir at low speed for 2-3 minutes to avoid fiber agglomeration and obtain concrete mix. S5. Pouring and curing: Pour the concrete mix into the mold, vibrate and compact it, smooth the surface, let it stand at room temperature until initial setting, cover it with a film to keep it moist for 7 days, and then let it cure naturally for 28 days to obtain the finished concrete.
9. The preparation method according to claim 8, characterized in that, In step S5, the vibration frequency is 40-50 Hz and the vibration time is 15-25 s; the curing environment temperature is 20-28℃ and the relative humidity is ≥90%.
10. The application of a high corrosion-resistant, impact-resistant, and wear-resistant concrete based on a geopolymer cementitious system as described in any one of claims 1 to 7, characterized in that, The concrete is used in the pouring and repair of flood discharge structures for water conservancy and hydropower, riverbank protection, splash zones of port wharves, chemical acid and alkali corrosion-resistant floors, wear-resistant road surfaces for mining transportation, and anti-corrosion structures for sewage treatment plants.